Data Mining: A Study on Data Cleaning Issues: Exploring Methods for Data Cleaning in Data Mining (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Data quality is a big problem in quality information management. Data quality create problems in information system. These issues are resolved by data cleaning. Data cleaning is a procedure used to determine incorrect, incomplete or unhelpful data and then upgrade the quality through correcting of make out errors and exceptions. Correcting errors and eliminating redundant records can be time taken and unexpected process but it cannot ignored. Data mining is a methods for locating useful information in data. Data quality mining is a current approach used data mining methods to identify and remove data quality issues in large databases. Data mining automatically express hidden and inherent information from the group of data. Data mining has various methods that are fitting for data cleaning.